2018
DOI: 10.1063/1.5024417
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative stress measurement of elastic deformation using mechanoluminescent sensor: An intensity ratio model

Abstract: The mechanoluminescent (ML) sensor is a newly developed non-invasive technique for stress/strain measurement. However, its application has been mostly restricted to qualitative measurement due to the lack of a well-defined relationship between ML intensity and stress. To achieve accurate stress measurement, an intensity ratio model was proposed in this study to establish a quantitative relationship between the stress condition and its ML intensity in elastic deformation. To verify the proposed model, experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Thus, the results of hypothesis testing indicate that the higher the decentralization, the more likely companies are to implement a management accounting system. This finding supports the contingency theory, which states that decentralization is related to the characteristics of management control systems (Chenhall, 2003). Decentralization also gives managers more responsibility and control in their activities and requires greater information as well (Waterhouse & Tjessen, 1978).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the results of hypothesis testing indicate that the higher the decentralization, the more likely companies are to implement a management accounting system. This finding supports the contingency theory, which states that decentralization is related to the characteristics of management control systems (Chenhall, 2003). Decentralization also gives managers more responsibility and control in their activities and requires greater information as well (Waterhouse & Tjessen, 1978).…”
Section: Discussionsupporting
confidence: 80%
“…The development of a charged surface on the phosphor during fracture results in an increase in recombination luminescence. [28,29]. An electric field of 10 7 -10 8 Vm À1 may be produced between oppositely charged surfaces.…”
Section: Studymentioning
confidence: 99%
“…When the load strikes the phosphor, a positive charge is built on one of the newly created surfaces, and a negative charge develops on the other cracked surface of the same phosphor. These charged particles produced an electric field that emitted electrons from the negatively charged surface and had an effect on the positively charged surface [29]. Therefore, luminous centres will be able to accommodate more electrons that recombine with holes already existing in the recombination centre.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…They found that SAOED has better ML stress-sensing properties than SAOE in terms of higher sensitivity and without saturation of ML intensity at applied forces . Similarly, Tao Cai et al proposed a quantitative model that gives the relation between the stress condition and its ML intensity . Newly discovered ML properties of rare earth ion-doped piezoelectric LiTaO 3 host materials attract engineers’ attention toward employing LiTaO 3 for ratiometric stress-sensing applications in several engineering domains. , However, the limited literature and less comprehensive ML studies of doped LiTaO 3 materials create barriers to its commercialization.…”
Section: Introductionmentioning
confidence: 99%